HUBUNGAN MOVEMENT BEHAVIOR DENGAN DURASI SCREEN TIME PADA SISWA/I SMP TARAKANITA CITRA RAYA SELAMA MASA PANDEMI TAHUN 2021 - Anissa Rachmavidia; Herwanto Herwanto (Journal Medical Universitas muhammadiyah Makassar, 2023)
The use of gadgets or screen time without paying attention to posture, screen brightness, and screen distance for a long time can affect vision and health. To reduce the spread of COVID-19, the Indonesian government has issued several social restrictions policies. As of September 5, 2021, Indonesians are advised to stay at home, the government has implemented school closures, and several sectors of the workplace are closed. These social restrictions result in children and families becoming increasingly dependent on screens for online learning, entertainment, and social interaction and have the potential to create barriers for society to comply with movement behavior recommendations. This cross sectional study aims to determine the relationship between physical activity, sleep duration, sedentary behavior, and movement behavior with the intensity of gadget use among students at Tarakanita Middle School during the 2021 pandemi. The sample size of this study was 239 students. The research method is filling out a questionnaire regarding movement behavior in accordance with the Canadian 24-h Movement Guidelines for Children and Youth (5-17 years) and a questionnaire on the intensity of the use of gadgets. Data were analyzed using chi-square analysis. The results of this study are that there is no relationship between physical activity and the intensity of smartphone use (p = 0.086), there is no relationship between sleep duration and the intensity of smartphone use (p = 0.810), there is a significant relationship between sedentary behavior and the intensity of smartphone use (p = 0.810). 0.000), and there is no relationship between movement behavior and the intensity of gadget use (p = 0.230). Parents, schools, and students are expected to pay more attention to the condition of sedentary behavior during the COVID-19 pandemi so as not to cause health problems in the future.